Pengaruh Kepemimpinan, Pengawasan, dan Motivasi Kerja terhadap Peningkatan Disiplin Guru Di SMP Negeri 16 Mandai Maros - Sumarni Mahmin; Haeder Haedar; Natsir Natsir (Pascasarjana STIE Amkop Makassar, 2018)
ABSTRAKThis study aims to determine how the influence of leadership, supervision and motivation of teacher discipline in SMP NEGERI 16 mandai marosThis research has been conducted in SMP NEGERI 16 mandai maros Starting from December 2017 until february 2018. The type of research used is descriptive quantitative with cross sectional approach. The sample in this research is 30 teachers in SMP NEGERI 16 mandai maros, sampling method in this research is accidental sampling where the sample will be taken while in the room and using the list of statements as a means of data collection. Statistical test used is multiple regression analysis with significant p level <0,05The results of this study indicate that the variables of leadership, supervision, and motivation affect the discipline of teachers. Where leadership variable with p value equal to 0,001 <0,05, control variable with p value equal to 0,00 <0,05, and variable of motivation with p value equal to 0,04 <0,05.There is a significant and simultaneous influence on leadership, supervision and motivation of teacher discipline at SMP NEGERI 16 Mandai MarosKeywords: Leadership, Supervision, Motivation, Teacher Discipline